2014
DOI: 10.1016/j.bjid.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremic pneumococcal pneumonia: serotype distribution, antimicrobial susceptibility, severity scores, risk factors, and mortality in a single center in Chile

Abstract: BPP had a high case-fatality rate in this group of adult patients with no association to resistant isolates, and a low immunization record. Three independent factors were related to death and the prognostic yield of different severity scores was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
0
15
0
7
Order By: Relevance
“…Previous studies have identified older age, [10] guideline-discordant antibiotic therapy, [9,11] and multilobe pneumonia, [11] as independent factors associated with increased BPP mortality. Our work confirms this and extends these findings to other markers of frailty beyond older age such as nursing home residence and community-dwelling dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified older age, [10] guideline-discordant antibiotic therapy, [9,11] and multilobe pneumonia, [11] as independent factors associated with increased BPP mortality. Our work confirms this and extends these findings to other markers of frailty beyond older age such as nursing home residence and community-dwelling dementia.…”
Section: Discussionmentioning
confidence: 99%
“…La serie completa ha sido publicada previamente 4 . Para cada caso se rescataron los gastos hospitalarios individuales desde el Departamento de Informática institucional.…”
Section: Pacientes Y Métodosunclassified
“…El grupo original estuvo compuesto por 60 eventos en 59 pacientes con 80% ≥ 60 años y la mitad sobre 75 años. El 76,3% tenía alguna co-morbilidad 4 .…”
Section: Pacientes Y Métodosunclassified
See 1 more Smart Citation
“…La vacunación contra S. pneumoniae no se acompaña de una activación de la enfermedad basal 81 . La vacuna conjugada 13-valente ofrece protección para aproximadamente 55 a 77% de los serotipos circulantes en el país y la vacuna polisacárida 23 valente para 77 a 95% de los serotipos circulantes en el país 82 .…”
Section: Vacuna Antineumocóccica En Pacientes Que Reciben Antagonistaunclassified